Analisis Strategi Pengembangan Pantai Ria Kenjeran Surabaya dalam Upaya Peningkatan Kunjungan Wisatawan - Habibi, Zidan Rifdi; Brilliana, Clora Widya; Fais, Moh Ainul; Cahyono, Wahyu Eko; Kunhadi, Dedy (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Coastal tourism plays a vital role in fostering regional economic growth while simultaneously strengthening local cultural identity. Nevertheless, the existing potential is often constrained by suboptimal management, as reflected in the case of Ria Kenjeran Beach in Surabaya, which faces limitations in facilities, weak promotional efforts, and competition with other destinations. This study employed the Delphi method to gather insights from experts and stakeholders, followed by analyses using IFAS, EFAS, SWOT, IE, and QSPM matrices to formulate suitable development strategies. The findings reveal that Ria Kenjeran Beach possesses significant internal strengths and considerable external opportunities, positioning it within the growth quadrant of the IE matrix. Furthermore, the QSPM analysis identified the top priority strategy as improving service quality and tourism activities, supported by infrastructure enhancement, digital promotion, and multi-stakeholder partnerships. These results highlight the necessity of integrated and sustainable strategies to strengthen Ria Kenjeran Beach as a leading coastal tourism destination in Surabaya.